A Study of Prevalence of Taenia Infestation and Associated Risk Factors Among the School Children of Dharan - Sah, Ram Bilakshan; Pokharel, PK; Paudel, IS; Acharya, A; Jha, N; Bhattarai, S (Kathmandu University Medical Journal, 2013)
Background Taenia prevalence has remained high among certain ethnic groups and occupational diseases in Nepal. Taenia saginata and Taenia solium species are worldwide in distribution. Infection is found most often in rural areas of developing countries with poor hygiene and living in close contact with pigs and eating undercooked pork meats. This allows the tapeworm infection to be completed and its cycle to continue. Objectives  To measure the prevalence of taenia infestation and to identify risk factors associated with taenia infestation among the school children of Dharan. Methods A cross sectional study was conducted among 935 Government and private school going children of Grade VI, VII, and VIII of Dharan during 2007 to 2008. Stratified random sampling method was applied to choose the schools and the study subjects. The prevalence was calculated, Chi-square test was used to measure the association of risk factors and taenia infestation. Results Taenia species was found to be high (5.5%) among the school children of Dharan. Infection rate of taenia among the male children (6.0%) was slightly higher than female (4.8%). There were no cases of taenia infestation found among children washing hands with soap. Regarding meat consumption in the non-vegetarian group, taenia infestation was found higher (6.5%) among pork eating than non-pork eating (4.7%). No significant relationship was traced among the factors in the causation of taenia infestation although slight indications present. Conclusion Taenia species was found very high among the school children of Dharan. No such association was found with the risk factors. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 14-17 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8011